Ice Cream: new virtual reality tool for the assessment of executive functions in children and adolescents: a normative study - Fernandez, Manuel Antonio; Rebon-Ortiz, Fidel; Saura-Carrasco, Miguel; Climent, Gema; Diaz-Orueta, Unai (Frontiers in Psychology, 2023)
This study focuses on the obtention of normative data for participants between 8 and 16 years old who were administered the Ice Cream test, a virtual reality tool designed to evaluate executive functions. The normative sample comprised n = 821 participants (49% female), with an age range of 8 to 16 years old, recruited across nine different testing sites in Spain. Experienced evaluators in psychological assessment, recruited and trained by the developer of the test, administered the test to the recruited sample. An empirical analysis of Ice Cream identified three factors, namely planning, learning and flexibility. Descriptive normative groups by age and gender were initially provided. A homoscedasticity analysis by gender showed no statistically significant differences between male and female participants. Cluster analysis by age suggested the creation of different age groups, respectively, 8 to 11 and 12 to 16 in Planning and Flexibility, and 8 to 9 and 10 to 16 in Learning, and subsequently, descriptive data for the established age groups per factor are shown. A confirmatory factor analysis showed the suitability of the 3 factors established as measured of three differentiated executive functions. Complementary data on the validity and reliability, and internal consistency of the scales are provided. Obtained normative data are relevant for evaluating executive functions in children and adolescents in a more ecological way. Further studies are needed to determine sensitivity and specificity of Ice Cream VR test to measure executive functions in different clinical populations.